Current state of transcatheter tricuspid valve repair - Kolte, Dhaval; Elmariah, Sammy (Cardiovascular Diagnosis and Therapy, 2019)
Tricuspid regurgitation (TR) is a common valvular heart disease affecting >1.6 million people in the United States (US) and >70 million people worldwide. The age- and sex-adjusted prevalence of more than or equal to moderate TR in the US is estimated to be 0.55%. One-year mortality increases with increasing severity of TR. Yet, the majority of patients with severe TR are managed medically in the absence of another indication for cardiac surgery, and isolated tricuspid valve (TV) surgery remains infrequent. To address this unmet clinical need, various transcatheter TV therapies are now being developed as an alternative to surgery in extreme- and high-risk patients with severe functional TR. Transcatheter TV repair devices are aimed at improving leaflet coaptation either directly by bringing the leaflets together (leaflet/coaptation devices) or indirectly by repairing the dilated annulus (annuloplasty devices). In this review, we describe the current state of transcatheter TV repair therapies and summarize the available data on the efficacy and safety of various devices. Procedural and clinical outcomes of transcatheter TV repair therapies are expected to improve in the coming years with technological advancement, newer device iterations, and increased experience in this field. Appropriate patient selection, optimal timing of intervention, and evaluation of long-term outcomes and device durability will be key in ongoing and future studies.